Chemotherapy Combined With Immunotherapy as a First-Line Treatment Brings Benefits to Patients With Lung Squamous Cell Carcinoma but Different Risks of Adverse Reactions: A Systematic Review and Meta-Analysis - Chen, Qian; Zhang, Zhen; Li, Xiaoli; Bu, Lingbiao (Frontiers in Pharmacology, 2022)
Objective To explore the efficacy and safety of chemotherapy combined with immunotherapy as the first-line treatment of advanced or metastatic squamous NSCLC. Methods Two researchers independently searched PubMed, the Cochrane Library, EMBASE, CNKI, Wanfang Data and other databases by computer, collected the clinical trials or randomized controlled trials published by April 2022 about immunotherapy combined with chemotherapy as the first-line treatment of advanced or metastatic squamous NSCLC, screened the literature and extracted the data according to the nanodischarge criteria. We used Revman5.4 for statistical analysis of the included studies. Results A total of 7 clinical trials were included, including 1510 cases in chemotherapy combined with immunotherapy group and 1519 cases in chemotherapy group. In terms of effectiveness, compared with chemotherapy group, chemotherapy combined with immunotherapy for advanced or metastatic squamous NSCLC had longer overall survival (HR = 1.59, 95% CI: 1.46-1.72, P < 0.00001) and progression free survival (HR = 1.84, 95% CI: 1.66-2.03, P < 0.00001). In terms of safety, the chemotherapy combined with immunotherapy group has a higher risk of adverse reactions at any level and above three levels of hematotoxicity, gastrointestinal abnormalities and liver dysfunction than the chemotherapy group. Conclusion Chemotherapy combined with immunotherapy is effective as the first-line treatment for advanced or metastatic squamous NSCLC, but the risk of adverse reactions is relatively high. If there are adverse reactions in clinical application, it should be treated in time.